Floral behaviour and unique autonomous self-pollination of Passiflora species (Passion fruit) - Ramaiya, S. D.; Bujang, J. S.; Zakaria, M. H. (Malaysian Society of Plant Physiology, 2019)
This paper presents the results of field studies conducted in Sarawak, Malaysia, to assess the flowering and pollination behaviours of Passiflora species, i.e. P. edulis (Purple), P. edulis (Frederick), P. maliformis, P. quadrangularis and P. incarnata, for yield and quality improvement and for other breeding programmes. It was shown that the Passiflora species exhibited constant production of few flowers within a day. The flowering behaviour varied among the species. The Passiflora flowers exhibited a unique autonomous self-pollination involving the movement of styles and anthers.